A more critical role for silicon in the catalytic Staudinger amidation: silanes as non-innocent reductants - Andrews, Keith G.; Denton, Ross M. (Royal Society of Chemistry, 2017)
Amides are ubiquitous in organic chemistry and occur in some of the most important natural and non-natural molecules such as peptides, pharmaceuticals and polymers.1 For this reason, amidation reactions are some of the most frequently carried out procedures in chemical synthesis.2 Amidation reactions between azides and carboxylic acid derivatives have found widespread application owing to the fact that they can be deployed in varied and complex reaction media.3,4,5 While many of these methods use carboxylic acid-derived activated esters, the phosphine-mediated amidation reaction between free acids and azides was reported in 1983 by Garcia and co-workers (Scheme 1A).6 The utility of the process is undermined somewhat by the production of triphenylphosphine oxide as a stoichiometric by-product. However, this problem was overcome in 2012 by Ashfeld and co-workers who reported a catalytic, traceless Staudinger ligation reaction (Scheme 1B).7 This process represents a combination of Garcia’s amidation with the work of O’Brien,8 who was the first to demonstrate chemoselective phosphine oxide reduction with phenylsilane in the context of a catalytic Wittig reaction.9–14 Given that the catalytic reaction was constructed on this basis, the authors proposed a catalytic cycle (Scheme 1C) involving two key steps: (a) phosphorus-mediated amidation via an aminophosphonium carboxylate and the reactive N,O-phosphorane; and (b) chemoselective silane-mediated phosphine oxide reduction to return the phosphine catalyst. While these two steps are established as discrete processes, their conflation into a catalytic cycle presents an intriguing chemoselectivity issue, namely the reduction of triphenylphosphine oxide in the presence of reductively labile iminophosphorane, aminophosphonium and N,O-phosphorane intermediates.15